N / O co-doped carbon bowl electrode material and preparation method and application thereof
By using N/O co-doped carbon bowl electrode material, the problems of poor H2O2 selectivity and slow reaction kinetics of existing catalysts under acidic conditions are solved, and efficient and stable H2O2 generation is achieved, which is suitable for large-scale promotion and application.
Patent Information
- Application Number
- CN202411556461.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing catalysts have poor selectivity of H2O2 under acidic conditions and are slow in reaction kinetics, making it difficult to promote and apply on a large scale.
Using N/O co-doped carbon bowl electrode material, the solid carbon nanospheres were etched with alkaline solution to obtain electrode materials with high ORR activity, excellent 2e-selectivity and long-term stability.
It significantly improves the selectivity of H2O2 in acidic conditions, accelerates the reaction kinetics, solves the problem of poor selectivity of existing catalysts under this condition, and is suitable for large-scale production and application.
Smart Images

Figure CN119409167A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to an N / O co-doped carbon bowl electrode material and a preparation method and application thereof. Background Art
[0002] At present, the production of industrial-grade hydrogen peroxide (H2O2) mainly relies on the traditional anthraquinone method, which is not only accompanied by the generation of undesirable byproducts, but also involves complex operating procedures. In view of this, on-demand electrocatalytic synthesis technology based on O2 is gradually attracting widespread attention from academia and industry due to its green, high efficiency and potential applications in disinfection, bleaching, wastewater treatment and other fields. The core mechanism of electrocatalytic H2O2 synthesis is to utilize O2 in the air to generate H2O2 through the two-electron oxygen reduction reaction (2e – ORR) directly converts O2 into H2O2. In this process, the acidic electrolyte environment shows significant advantages over the alkaline medium, because H2O2 is more stable under acidic conditions and can directly use its strong oxidizing property to achieve on-site remediation of polluted water bodies. – ORR faces the dual challenges of sluggish reaction kinetics and low selectivity of the two-electron pathway, which has long restricted the further development of this technology.
[0003] For electrocatalysis 2e – Existing research on ORR catalysts covers a variety of types, including precious metals, non-precious metals, single atoms and carbon-based catalysts. Among them, carbon-based metal-free catalysts have become a hot topic in the field of electrocatalytic ORR preparation of H2O2 due to their low cost, excellent conductivity, adjustable physical and chemical properties and high stability in acidic environments. Although most metal-free carbon catalysts exhibit high catalytic performance under alkaline conditions, considering the easy decomposition of H2O2 in alkaline solutions and its higher practical value in acidic media, it is particularly important to develop metal-free carbon catalysts suitable for acidic conditions. It is worth noting that the participation of protons significantly reduces the energy barrier for the breakage of the O–OH bond (about 0.14 eV), while the energy barrier for the breakage of the *–O bond remains unchanged. This is the fundamental reason for the low selectivity of carbon-based catalysts to generate H2O2 under current acidic conditions, and it is also a major bottleneck for the application of metal-free carbon catalysts in acidic environments.
[0004] Secondly, the electrode design for acidic electrosynthesis of H2O2 is also crucial. Studies have shown that the use of gas diffusion electrodes that facilitate O2 diffusion is beneficial to the production of H2O2. By optimizing the gas flow rate in the gas diffusion chamber and the applied current density, the production efficiency of H2O2 can be improved, and higher kinetic rates and H2O2 accumulation yields are achieved at high current densities. Although gas diffusion electrodes have outstanding advantages in mass transfer and have been proven to exhibit excellent performance when applied to H2O2 production, there are still some potential challenges and limitations that need to be overcome, such as poor electrode stability and poor adaptability to strong acid environments, which make it difficult to successfully apply them on a large scale.
[0005] Therefore, the development of metal-free carbon catalysts and electrodes with high ORR activity, excellent 2e-selectivity and long-term stability is of great significance for promoting the acidic electrosynthesis technology of H2O2 towards practical application. Summary of the invention
[0006] In view of this, the present invention provides a N / O co-doped carbon bowl electrode material and a preparation method and application thereof to solve the problems of poor H2O2 selectivity, sluggish reaction kinetics and difficulty in large-scale promotion and application of existing catalysts (electrode materials) under acidic conditions.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a N / O co-doped carbon bowl electrode material comprises the following steps:
[0009] 1) mixing aqueous ammonia, silicon alkoxide, alcohol and water to obtain a mixed solution;
[0010] 2) mixing the mixed solution, resorcinol and formaldehyde solution, and then centrifuging to obtain a precipitated sample, and annealing the precipitated sample to obtain solid carbon nanospheres;
[0011] 3) etching the solid carbon nanospheres with an alkaline solution to obtain a N / O co-doped carbon bowl electrode material;
[0012] The etching reaction time in step 3) is 90 to 100 hours.
[0013] Preferably, the volume ratio of ammonia water, silicon alkoxide, alcohol and water in step 1) is 2.5-3.5:3-4:65-75:5-15.
[0014] Preferably, the mass concentration of the ammonia water is 28-30%.
[0015] Preferably, the silicon alkoxide includes one or more of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane and tetrabutoxysilane.
[0016] Preferably, the ratio of the amount of resorcinol and formaldehyde solution added in step 2) to the amount of silicon alkoxide in the mixed solution is 0.35-0.45 g: 0.5-0.6 ml: 65-75 ml;
[0017] The mass concentration of the formaldehyde solution is 35-40%.
[0018] Preferably, the annealing temperature in step 2) is 650-750° C., and the annealing time is 2-3 hours.
[0019] Preferably, the pH value of the alkaline solution in step 3) is 13-14.
[0020] Preferably, the alkaline solution in step 3) comprises one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution.
[0021] Another object of the present invention is to provide an N / O co-doped carbon bowl electrode material prepared by the preparation method.
[0022] Another object of the present invention is to provide an application of a N / O co-doped carbon bowl electrode material in the electrocatalytic synthesis of H2O2 in an acidic environment.
[0023] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Innovative electrode materials: The N / O co-doped carbon bowl electrode material disclosed in the present invention is a new type of electrode material with unique physical and chemical properties, providing new options and research directions for the field of electrochemistry;
[0025] 2. Accelerate reaction kinetics: The design and optimization of the electrode material helps to accelerate the kinetics of the relevant chemical reactions, thereby improving the overall reaction efficiency and performance;
[0026] 3. Improve the selectivity of H2O2: Through the design of N / O co-doped carbon bowl electrode materials, the present invention can significantly improve the selectivity of generating H2O2 under acidic conditions, solving the problem of poor selectivity of existing catalysts under this condition;
[0027] 4. Easy to promote and apply on a large scale: The preparation method provided by the present invention is relatively simple, economical, and suitable for large-scale production, which helps to solve the problem that the existing technology is difficult to promote and apply on a large scale;
[0028] 5. Broaden the scope of application: Due to the improved selectivity and reaction kinetics of H2O2, this new electrode material may be suitable for a wider range of electrochemical applications, such as electrochemical synthesis, environmental purification, energy storage and other fields. In summary, compared with traditional electrode materials, the carbon bowl electrode prepared by the present invention makes up for the defects and deficiencies of traditional carbon electrodes, realizes the optimization of electrode structure and the expansion of electrochemical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 This is a scanning electron microscope image of the nitrogen and oxygen co-doped hollow carbon nanobowl HCB (N / O) prepared in Example 1 of the present invention;
[0031] Figure 2 The particle size distribution histogram of the nitrogen and oxygen co-doped hollow carbon nanobowl HCB (N / O) prepared in Example 1 of the present invention;
[0032] Figure 3 This is a high-magnification transmission electron microscopy image of the nitrogen-oxygen co-doped hollow carbon nanobowl HCB (N / O) prepared in Example 1 of the present invention;
[0033] Figure 4 The H2O2 yield and Faraday efficiency of the N / O co-doped carbon bowl electrode prepared in Example 1 at different voltages;
[0034] Figure 5 H2O2 yield and Faraday efficiency of the electrode prepared based on Comparative Example 1 at different voltages;
[0035] Figure 6 H2O2 yield and Faraday efficiency of the electrode prepared based on Comparative Example 2 at different voltages;
[0036] Figure 7 H2O2 yield and Faraday efficiency of the electrode prepared based on Comparative Example 3 at different voltages;
[0037] Figure 8 This is a diagram of H2O2 production stability based on the N / O co-doped carbon bowl electrode prepared in Example 1;
[0038] Fig. 9 This is the 24h cumulative production diagram of H2O2 at a voltage of -0.5V for N / O co-doped carbon bowl electrode;
[0039] Fig.10This is the effect diagram of N / O co-doped carbon bowl electrode used for in situ electro-Fenton contaminated water remediation. DETAILED DESCRIPTION
[0040] The present invention provides a method for preparing a N / O co-doped carbon bowl electrode material, comprising the following steps:
[0041] 1) mixing aqueous ammonia, silicon alkoxide, alcohol and water to obtain a mixed solution;
[0042] 2) mixing the mixed solution, resorcinol and formaldehyde solution, and then centrifuging to obtain a precipitated sample, and annealing the precipitated sample to obtain solid carbon nanospheres;
[0043] 3) The solid carbon nanospheres are subjected to an etching reaction with an alkaline solution to obtain a N / O co-doped carbon bowl electrode material.
[0044] In the present invention, the N / O co-doped carbon bowl electrode material is a metal-free carbon catalyst.
[0045] In the present invention, the etching reaction time in step 3) is 90 to 100 hours, specifically 91 hours, 92 hours, 94 hours, 95 hours, 96 hours, 98 hours, and 99 hours; the present invention can obtain carbon materials with different specific morphologies by controlling the time adjustment of the etching reaction. When the etching time is about 24 hours, egg yolk-shaped carbon nanospheres are obtained, when the etching time is adjusted to about 72 hours, hollow carbon nanospheres can be obtained, and when the etching time is adjusted to the time specified in the present invention, hollow carbon nanobowls can be obtained.
[0046] In the present invention, the volume ratio of ammonia water, silicon alkoxide, alcohol and water in step 1) is 2.5-3.5:3-4:65-75:5-15, preferably 2.8-3.2:3.2-3.6:68-72:8-12, and more preferably 3:3.5:70:10.
[0047] In the present invention, the mass concentration of the ammonia water is 28-30%, specifically 28.5%, 29%, and 29.5%. By adjusting the concentration of the ammonia water, the present invention can directionally regulate the nitrogen content in the N / O co-doped carbon bowl electrode material, and the nitrogen content and etching time are synchronized to achieve the optimization of the catalyst morphology.
[0048] In the present invention, the alcohol includes one or more of methanol, ethanol and propanol.
[0049] In the present invention, the silicon alkoxide includes one or more of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane and tetrabutoxysilane.
[0050] In the present invention, the ratio of the amount of resorcinol and formaldehyde solution added in step 2) to the amount of silicon alkoxide in the mixed solution is 0.35-0.45 g: 0.5-0.6 ml: 65-75 ml, preferably 0.38-0.42 g: 0.52-0.56 ml: 68-72 ml, and more preferably 0.4 g: 0.55 ml: 70 ml.
[0051] In the present invention, the mass concentration of the formaldehyde solution is 35-40%, specifically 36%, 37%, 38%, 39%.
[0052] In the present invention, in step 2), the mixed solution and resorcinol are preferably mixed first, mixed for 8 to 15 minutes, and then mixed with the formaldehyde solution; the specific interval time can be 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, or 14 minutes.
[0053] In the present invention, the temperature of the annealing treatment in step 2) is 650-750°C, specifically 660°C, 680°C, 700°C, 720°C, 740°C; the time of the annealing treatment is 2-3h, specifically 2.2h, 2.4h, 2.5h, 2.6h, 2.8h.
[0054] In the present invention, the pH value of the alkaline solution in step 3) is 13-14, specifically 13.2, 13.4, 13.5, 13.6, or 13.8.
[0055] In the present invention, the alkaline solution in step 3) includes one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution.
[0056] The present invention also provides an N / O co-doped carbon bowl electrode material prepared by the preparation method.
[0057] The present invention also provides an application of a N / O co-doped carbon bowl electrode material in electrocatalytic synthesis of H2O2 in an acidic environment.
[0058] In the present invention, the application of the N / O co-doped carbon bowl electrode material is preferably used to prepare the N / O co-doped carbon bowl electrode.
[0059] In the present invention, the preparation method of the N / O co-doped carbon bowl electrode comprises:
[0060] The N / O co-doped carbon bowl electrode material, alcohol and Nafion 117 solution are mixed to obtain catalyst ink; the catalyst ink is then coated on hydrophobic carbon paper to obtain the N / O co-doped carbon bowl electrode.
[0061] In the present invention, the N / O co-doped carbon bowl electrode is a gas diffusion electrode having excellent gas affinity and oxygen mass transfer capability.
[0062] In the present invention, the mass volume ratio of N / O co-doped carbon bowl electrode material, alcohol and Nafion 117 solution is 3-5 mg: 970-990 μL: 10-30 μL, preferably 4-5 mg: 980-990 μL: 20-30 μL, and more preferably 5 mg: 990 μL: 10 μL.
[0063] In the present invention, the alcohol includes ethanol and / or isopropanol.
[0064] In the present invention, the loading amount of N / O co-doped carbon bowl electrode material on the hydrophobic carbon paper is 200-300 μg / cm 2 , specifically 220 μg / cm 2 , 240μg / cm 2 , 250μg / cm 2 , 260μg / cm 2 , 280μg / cm 2 .
[0065] In the present invention, the electrocatalytic synthesis of H2O2 in an acidic environment preferably uses a N / O co-doped carbon bowl electrode as a working electrode and a Pt sheet as a counter electrode. The two electrodes are separated by a proton exchange membrane and are located in the counter electrode chamber and the working electrode chamber, respectively.
[0066] In the present invention, the catalytic voltage of the working electrode for electrocatalytic synthesis of H2O2 in an acidic environment is -0.6 to -0.4V, specifically -0.58V, -0.55V, -0.52V, -0.5V, -0.48V, -0.45V, -0.42V.
[0067] In the present invention, the pH value of H2O2 electrocatalytic synthesis in an acidic environment is 0.7-3, specifically 0.8, 1, 1.5, 2, 2.5.
[0068] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] A mixed solution containing 70 ml of ethanol, 10 ml of deionized water, 3 ml of ammonia water (30 wt.%) and 3.46 ml of tetraethyl orthosilicate was stirred for 15 min; 0.4 g of resorcinol was added to the above mixture and mixed, and 0.56 ml of formaldehyde solution (37 wt.%) was added after 10 min, and the mixture was ultrasonically mixed and stirred at room temperature for 24 h; after stirring, the mixture was centrifuged at 7000 rpm for 3 min to collect the precipitated sample; the collected sample was annealed in N2 conditions at 700 ° C for 2 h (heating rate of 5.8 ° C / min) to obtain a solid carbon nanosphere (SCS) sample; SCS was alkaline etched with NaOH solution (pH value is 13), and the etching time was controlled to be 96 h, and nitrogen-oxygen co-doped hollow carbon nanobowl (HCB (N / O)), that is, N / O co-doped carbon bowl electrode material, was obtained.
[0071] The morphology and structure of the obtained N / O co-doped carbon bowl electrode material were characterized. The scanning electron microscopy (SEM) characterization results are as follows: Figure 1 As shown, through Figure 1 It can be seen that during the alkaline etching process, the structure of the catalyst did not show obvious collapse and particle size changes, and HCB (N / O) showed an obvious bowl-shaped structure. Subsequently, Image.J software was used to perform particle size statistical analysis on the SEM results of the catalyst. The statistical results are as follows: Figure 2 As shown, through Figure 2 It can be seen that the average particle size of the HCB (N / O) catalyst is about 200nm, and the particle size distribution is uniform. The uniform morphology characterization results prove that the prepared catalyst has no obvious aggregation or dispersion phenomenon, and the preparation process is well controlled. Such uniform distribution can also provide a more uniform catalyst active surface and promote more consistent reaction efficiency. High-magnification transmission electron microscopy (STEM) results also prove that the HCB (N / O) catalyst presents a complete and clear bowl-shaped structure (see Figure 3 ), compared with spherical catalysts, the construction of bowl-shaped structure is conducive to increasing specific surface area and changing heteroatom content, promoting fast and efficient interfacial mass transfer, and improving ORR performance. In addition, the aberration-corrected element scanning STEM and corresponding STEM-mapping further confirmed the uniform distribution of C, N, and O elements in HCB.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is that the etching time is adjusted to 24 h, and egg yolk-shaped carbon nanospheres (YCS) are obtained.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 1 is that the etching time is adjusted to 72 hours to obtain hollow carbon nanospheres (HCS).
[0076] Comparative Example 3
[0077] The difference between this comparative example and Example 1 is that the concentration of ammonia water is adjusted to 10 wt.%, and oxygen-doped hollow carbon nanobowls (HCB(O)) are obtained. The concentration of ammonia water is adjusted to 10 wt.%, and no nitrogen doping is included.
[0078] Experimental Example 1
[0079] 5 mg of the N / O co-doped carbon bowl electrode material prepared in Example 1 was mixed with 990 μL of ethanol and 10 μL of Nafion 117 solution (~3 wt%), and ultrasonicated for 1 h to obtain a uniformly dispersed catalyst ink (the solution temperature in the ultrasonic system was kept at room temperature during the ultrasonic treatment to prevent the catalyst ink from agglomerating); 200 μL of the uniformly dispersed catalyst ink (the loading amount of the N / O co-doped carbon bowl electrode material was 250 μg / cm 2 ); The prepared carbon paper electrode was naturally dried at room temperature for 12 h to obtain an independent gas-diffused N / O co-doped carbon bowl electrode.
[0080] Electrocatalytic synthesis of H2O2 in an acidic environment: A flow cell reactor made of organic glass (PMMA) was used, the gas diffusion N / O co-doped carbon bowl electrode was used as the working electrode, and a Pt sheet was used as the counter electrode (area: 4 cm 2 ), the working electrode and the counter electrode were located in the working electrode chamber and the counter electrode chamber, respectively. The two chambers were separated by a proton exchange membrane (Nafion 117 membrane, Sigma-Aldrich). Dual pressure pumps were used to realize the flow circulation of the electrolytes at both electrodes. The electrolyte was a sulfuric acid aqueous solution (pH = 0.7). The electrochemical production performance of H2O2 under flowing water was investigated. During the operation, pressure pumps were used in both the counter electrode chamber and the working electrode chamber to realize the circulation of the electrolytes at a flow rate of 5 mL h -1 . In addition, the oxygen in the serpentine chamber is transported to the gas diffusion layer side in a flowing manner to alleviate the limited solubility of oxygen. The production of H2O2 was tested by the time chronoamperometry (CA, it curve of the electrochemical workstation). The input voltage was calibrated according to the reference electrode. The potassium titanium oxalate method was used to test the H2O2 concentration during the operation of the equipment, and the test was performed at intervals using a UV-visible spectrophotometer (λ=400nm). First, 0.5mL of electrolyte, 0.5mL of H2SO4 (3M), 1mL of ultrapure water and 0.5mL of potassium titanium oxalate (0.1M) were mixed, and the absorbance was measured with a UV-visible spectrophotometer after standing for 1min, and the H2O2 concentration was calculated according to the calibration curve. The Faraday efficiency (FE) of H2O2 production in the flow cell reactor was calculated by formula 1, where nH2O2 is the molar amount of H2O2 produced and 2 represents 2e -The number of electrons transferred during the ORR reaction, 96485 is the Faraday efficiency, and Q is the amount of electricity consumed during the reaction.
[0081] Formula 1:
[0082] For the N / O co-doped carbon bowl electrode, the H2O2 production yield increases with the catalytic voltage from 0 V to -0.5 V, remains high in the range of -0.6 to -0.4 V, and reaches the maximum H2O2 production yield (2942.4 mg L –1 h –1 ), at the same time, the Faraday efficiency also increases and reaches the maximum (92%) at -0.5V. The specific results are as follows Figure 4 shown.
[0083] The catalyst electrode materials obtained in Comparative Examples 1 to 3 were tested using the same testing method as in Example 1. The test results correspond to Figures 5 to 7 ,pass Figures 5 to 7 It can be seen that compared with the N / O co-doped carbon bowl electrode, the YCS, HCS and HCB(O) electrodes all have relatively lower H2O2 production yields and lower Faradaic efficiencies, which once again verifies the excellent performance of the N / O co-doped carbon bowl electrode protected by this patent. This excellent performance comes from its excellent N / O co-doping properties and optimized bowl structure.
[0084] Experimental Example 2
[0085] A flow cell reactor made of organic glass (PMMA) was used, a N / O co-doped carbon bowl electrode was used as the working electrode, and a custom Pt sheet was used as the counter electrode (area: 4 cm 2 ), the two chambers were separated by a proton exchange membrane (Nafion 117 membrane, Sigma-Aldrich), and dual pressure pumps were used to realize the flow circulation of the two-electrode electrolyte. The electrolyte was a sulfuric acid aqueous solution (pH 0.7). The electrochemical production performance of H2O2 under flowing water was investigated. During the operation, pressure pumps were used to realize the circulation of electrolyte in both the counter electrode chamber and the working electrode chamber, with a flow rate of 5 mL h -1 In addition, the oxygen in the serpentine chamber is transported to the gas diffusion layer side in a flowing manner to alleviate the limited solubility of O2. The catalytic stability of the N / O co-doped carbon bowl electrode was measured at a fixed potential by the chronoamperometric response curve (IT curve). When a voltage of -0.5 V was applied, the current response was as follows: Figure 8 As shown, the flow cell reactor can achieve a current response of ~80 mA. After running for 76 hours, there is basically no obvious attenuation of the current, and the H2O2 yield is basically unchanged, maintaining at a high level, demonstrating the unique acid resistance and excellent stability of the N / O co-doped carbon bowl electrode.
[0086] Although great progress has been made in the alkaline production of H2O2, H2O2 is difficult to store and easily decomposes under alkaline conditions, which limits its application under alkaline conditions. H2O2 produced in acidic systems can be used for disinfection and Fenton reactions. The use of 0.5-3wt.% H2O2 can also play a key role in reducing hospitalization rates and complications. Therefore, in addition to exploring the H2O2 production yield and stability of the catalyst in acid, its cumulative production output was tested. The N / O co-doped carbon bowl electrode was used to test the cumulative production of H2O2 under an applied voltage of -0.5V. The test results are as follows: Fig. 9 As shown in Figure 2, H2O2 production accumulates over time. After 24 h of accumulation, the H2O2 production concentration can reach 7100 mg L -1 (~0.7wt.%), which is an H2O2 concentration that can meet the basic disinfection and actual Fenton reaction requirements.
[0087] Experimental Example 3
[0088] The N / O co-doped carbon bowl electrode is used in the in-situ electro-Fenton system to achieve in-situ remediation of polluted water bodies. The construction of the Fenton system is based on the H2O2 production test experiment. The specific operation is carried out according to the following steps: (1) The Fenton system of the flow cell reactor consists of a three-electrode system, and the working electrode is a N / O co-doped carbon bowl electrode (area: 2*2cm 2 ), the reference electrode is Ag / AgCl reference electrode, and the counter electrode is a Pt sheet (area: 2*2cm 2 ); (2) Select a flow cell reactor made of organic glass (PMMA), and use a proton exchange membrane to separate the working electrode chamber and the counter electrode chamber (the reference electrode is located in the cathode chamber); (3) Adjust the pH value of the solution: Add the pollutant wastewater to be treated on one side of the electrolytic cell, and adjust the pH value of the solution (pH value is 0.7) to promote the Fenton reaction. Select a pollutant solution prepared with H2SO4 electrolyte solution to simultaneously build an acidic system; (4) Add substrate: Prepare an appropriate amount of iron salt, which is the key reagent of the Fenton reaction. In this work, H2O2 is synthesized by in-situ electrocatalysis. Before the experiment begins, it is necessary to add an appropriate amount of divalent iron to the working electrode chamber; (5) Apply voltage: Use an electrochemical workstation to apply a suitable voltage to promote the electrocatalytic reaction. Among them, the applied voltage is the voltage condition for the optimal production of H2O2 (-0.5V vs. RHE); (6) Setting up an oxygen supply system: to ensure that there is enough oxygen participating in the reaction process; (7) Effect monitoring: during the entire reaction process, monitor the progress of the reaction, including parameters such as the degradation rate and degradation effect of the pollutants.
[0089] Three types of pollutants were selected as model pollutants for Fenton degradation. The specific types and concentrations are as follows: three dye wastewaters: methylene blue (MB, 20 mg L –1 ), Rhodamine B (RhB, 20 mg L –1 ) and malachite green (MG, 20 mg L –1 ); three kinds of pharmaceutical wastewater: carbamazepine (CBZ, 1 mg L –1 ), sulfadiazine (SDZ, 1 mg L –1 ) and tetracycline (TC, 1 mg L –1 ) and three phenolic wastewaters: phenol (PH, 1 mg L –1 ), p-chlorophenol (P-CH, 1 mg L –1 ) and p-nitrophenol (PNP, 1 mg L –1 ) and other target pollutants in the electro-Fenton reaction system. A voltage of -0.5 V was applied using the three-electrode system of the electrochemical workstation. 100 mg of Fe was added to the pollutant solution before the reaction started. 2+ The in-situ electro-Fenton degradation effect of N / O co-doped carbon bowl electrode on 9 different types of pollutants is shown in Figure 2. Fig.10 As shown, it proves that it has a good degradation effect on various types of pollutants.
[0090] Example 2
[0091] A mixed solution containing 65 ml of ethanol, 5 ml of deionized water, 3.5 ml of ammonia water (28.5 wt.%) and 4 ml of tetraethyl orthosilicate was stirred for 15 min; 0.35 g of resorcinol was added to the above mixture and mixed, and 0.5 ml of formaldehyde solution (35 wt.%) was added after 15 min, and the mixture was ultrasonically mixed and stirred at room temperature for 24 h; after stirring, the mixture was centrifuged at 7000 rpm for 3 min to collect the precipitated sample; the collected sample was annealed at 650 ° C in N2 conditions for 3 h (heating rate of 5.8 ° C / min) to obtain a solid carbon nanosphere (SCS) sample; SCS was alkaline etched with NaOH solution (pH value of 13.5), and the etching time was controlled to be 100 h, and nitrogen-oxygen co-doped hollow carbon nanobowl (HCB (N / O)), that is, N / O co-doped carbon bowl electrode material, was obtained.
[0092] Example 3
[0093] A mixed solution containing 75 ml of propanol, 15 ml of deionized water, 2.5 ml of ammonia water (28.5 wt.%) and 3 mL of tetramethoxysilane was stirred for 15 min; 0.45 g of resorcinol was added to the above mixture and mixed, and 0.6 mL of formaldehyde solution (40 wt.%) was added after 8 min, and the mixture was ultrasonically mixed and stirred at room temperature for 24 h; after stirring, the mixture was centrifuged at 7000 rpm for 3 min to collect the precipitated sample; the collected sample was annealed in N2 conditions at 750 ° C for 2.5 h (heating rate of 6 ° C / min) to obtain a solid carbon nanosphere (SCS) sample; SCS was alkaline etched with NaOH solution (pH value of 14), and the etching time was controlled to be 92 h, so that nitrogen and oxygen co-doped hollow carbon nanobowls (HCB (N / O)), i.e., N / O co-doped carbon bowl electrode materials, could be obtained.
[0094] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0095] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a N / O co-doped carbon bowl electrode material, characterized in that: The steps include: 1) mixing aqueous ammonia, silicon alkoxide, alcohol and water to obtain a mixed solution; 2) mixing the mixed solution, resorcinol and formaldehyde solution, and then centrifuging to obtain a precipitated sample, and annealing the precipitated sample to obtain solid carbon nanospheres; 3) etching the solid carbon nanospheres with an alkaline solution to obtain a N / O co-doped carbon bowl electrode material; The etching reaction time in step 3) is 90 to 100 hours.
2. The method for preparing a N / O co-doped carbon bowl electrode material according to claim 1, characterized in that: The volume ratio of ammonia water, silicon alkoxide, alcohol and water in step 1) is 2.5-3.5:3-4:65-75:5-15.
3. The method for preparing a N / O co-doped carbon bowl electrode material according to claim 2, characterized in that: The mass concentration of the ammonia water is 28-30%.
4. The method for preparing a N / O co-doped carbon bowl electrode material according to any one of claims 1 to 3, characterized in that: The silicon alkoxide includes one or more of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane and tetrabutoxysilane.
5. The method for preparing a N / O co-doped carbon bowl electrode material according to claim 4, characterized in that: The ratio of the amount of resorcinol and formaldehyde solution added in step 2) to the amount of silicon alkoxide in the mixed solution is 0.35-0.45 g: 0.5-0.6 ml: 65-75 ml; The mass concentration of the formaldehyde solution is 35-40%.
6. The method for preparing a N / O co-doped carbon bowl electrode material according to claim 5, characterized in that: The temperature of the annealing treatment in step 2) is 650-750° C., and the annealing treatment time is 2-3 hours.
7. The method for preparing a N / O co-doped carbon bowl electrode material according to claim 5 or 6, characterized in that: The pH value of the alkaline solution in step 3) is 13-14.
8. The method for preparing a N / O co-doped carbon bowl electrode material according to claim 7, characterized in that: The alkaline solution in step 3) includes one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution.
9. The N / O co-doped carbon bowl electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the N / O co-doped carbon bowl electrode material according to claim 9 in electrocatalytic synthesis of H2O2 in an acidic environment.
Citation Information
Cited By
Preparation method, product and application of boron-doped hollow carbon spheres
CN120887403A